(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2020)
In the Chilean education system, the development of teaching skills for the effective implementation of the Technical and Vocational Secondary Education curriculum is a critical aspect. This paper examines different laws and regulations, including the Teacher Professional Development System, depending on the requirements, needs and particularities of technical teachers. The analysis is carried out base on the conception of equity as fair respect for differences, in four dimensions: requirements for teaching, initial teacher education, continuous teacher training, and professional evaluation and recognition. We identify various inequities that make technical teachers are in a disadvantage for progressing in their teaching career that associate different career stages to professional development prospects and wages. Keywords: Teachers. Technical and vocational secondary education. Equity.